Distribution Exclusivity in the Formation of Premium Product Image - Darmawan, Didit; Izza, Nailul (Journal of Fundamental Management (JFM), 2026)
This literature review examines how distribution exclusivity functions as a mechanism for shaping consumer perception of value and quality in premium products. The study employs a qualitative literature review method, synthesizing theoretical perspectives from marketing management, consumer behavior, and brand strategy literature. The analysis reveals that distribution exclusivity operates through psychological mechanisms such as the scarcity principle, which increases desire and appreciation, as well as sociological mechanisms where products become markers of identity and social status. Store location selectivity, rigorous partner selection, and scarcity management create signals that consumers interpret as indicators of product specialness. Simultaneously, premium product manufacturers must navigate the tension between maintaining exclusivity and meeting market accessibility needs through distribution hierarchies, supply management, exclusive membership programs, and innovative distribution models including pop-up stores and selective digital platform partnerships. The theoretical contribution lies in expanding understanding of distribution's symbolic dimensions in value perception formation. Practically, this review suggests that companies should integrate distribution strategy with overall brand strategy, select partners based on value alignment, design inclusive communication about exclusivity, and innovate new forms of exclusivity relevant to modern consumer behavior. Successful management of these dynamics enables manufacturers to build premium brands sustained by both product quality and the distinctive meanings attached to the ownership experience.